2017
DOI: 10.5194/tc-11-1733-2017
|View full text |Cite
|
Sign up to set email alerts
|

Experimental observation of transient <i>δ</i><sup>18</sup>O interaction between snow and advective airflow under various temperature gradient conditions

Abstract: Abstract. Stable water isotopes (δ 18 O) obtained from snow and ice samples of polar regions are used to reconstruct past climate variability, but heat and mass transport processes can affect the isotopic composition. Here we present an experimental study on the effect of airflow on the snow isotopic composition through a snow pack in controlled laboratory conditions. The influence of isothermal and controlled temperature gradient conditions on the δ 18 O content in the snow and interstitial water vapour is el… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 61 publications
(82 reference statements)
5
19
0
Order By: Relevance
“…However, our observations and modelling results appear to disagree with this approach, mainly due to the fact that the fractionation coefficients are only able to describe thermodynamic equilibrium conditions, which were not met in our case study. These in situ field results validate previous laboratory studies from Sokratov and Golubev (2009) and Ebner et al (2017), which also showed that thermodynamic equilibrium conditions were not able to describe the exchanges between snow and vapour.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…However, our observations and modelling results appear to disagree with this approach, mainly due to the fact that the fractionation coefficients are only able to describe thermodynamic equilibrium conditions, which were not met in our case study. These in situ field results validate previous laboratory studies from Sokratov and Golubev (2009) and Ebner et al (2017), which also showed that thermodynamic equilibrium conditions were not able to describe the exchanges between snow and vapour.…”
Section: Discussionsupporting
confidence: 82%
“…Isotope exchanges during snow metamorphism and diffusion within the porous matrix of the subsurface snowpack additionally affect snow isotopic composition (Langway, 1970;Johnsen, 1977;Whillans and Grootes, 1985;Calonne et al, 2015;Ebner et al, 2017) and the diffusion length depends on the firn ventilation, the snow density, porosity and tortuosity and the exchange rate between the atmospheric water vapour and the surface snow (Johnsen et al, 2000;Gkinis et al, 2014). This large variety of processes hampers isotopic signal interpretation.…”
Section: Atmospheric Boundary Layermentioning
confidence: 99%
See 1 more Smart Citation
“…Isotopes have recently been implemented in the complex snowpack model CROCUS (Touzeau et al, 2018). The authors propose, similar to Ebner et al (2017), that a snow grain has an inner and outer isotopic composition, which is similar upon snowfall, but changes independently as the snow grain undergoes postdepositional processes. We propose that throughout a single day, the outer snow grain undergoes substantial changes in both volume and isotopic composition, whereas the inner snow grain isotopic composition stays constant.…”
Section: 1029/2018jd029619mentioning
confidence: 88%
“…Recent studies have shown, however, that the in-E. Schlosser et al: Influence of the synoptic regime on stable water isotopes in precipitation at Dome C teraction between the uppermost layers of the snowpack and the overlying atmosphere between precipitation events also plays an important role. This was found in both Greenland Bonne et al, 2014) and Antarctica (Casado et al, 2016a, b;Ritter et al, 2016;Touzeau et al, 2016) as well as in laboratory experiments (Ebner et al, 2017).…”
Section: Ice Cores In Paleoclimatologymentioning
confidence: 94%